84.6k views
0 votes
Use the formula M = NPQ to solve for the following variables.

a. Solve for N.

b. Solve for Q.

User Bldoron
by
6.0k points

2 Answers

7 votes

Explanation:

M=NPQ

m/pq=Npq/pq

pq is going to cancel, you left with N

N= m/pq

To solve for q, we have to make q the subject.

m = Npq

divide both sides of the equation by NP

M/NP= q

that's the answer

User Kunal Shaktawat
by
5.4k points
6 votes

Answer:

N = M/(PQ)

Q = M/(NP)

Explanation:

Given that

M = NPQ

  • then if we divide by PQ at both sides of the equation

M/(PQ) = NPQ/(PQ)

M/(PQ) = N

  • On the other hand, if we divide by NP at both sides of the equation

M/(NP) = NPQ/(NP)

M/(NP) = Q

User McLan
by
5.7k points